Factors associated with undiagnosed diabetes mellitus among the peka B40 population on Langkawi Island from 2022 to 2023 - Kamarudin, Syuaib Aiman Amir (2024)
Introduction: The prevalence of undiagnosed DM poses a significant public health challenge, particularly among socio-economically disadvantaged populations. This study aims to evaluate the prevalence and factors associated with undiagnosed DM among the PeKa B40 population on Langkawi Island, Malaysia. Methodology: A retrospective cross-sectional study was conducted using secondary data records from January 2022 to December 2023, involving 1,070 participants from the PeKa B40 population on Langkawi Island. Participants were previously screened for DM using fasting blood glucose tests and HbA1c levels as part of the PeKa B40 initiative. Sociodemographic data, current health status, lifestyle factors, family history, and medical history were extracted from the existing Peka B40 records. Descriptive statistics were used to summarize the data, and multiple logistic regression analyses were performed to identify factors associated with undiagnosed DM. Results: The prevalence of undiagnosed DM was found to be 6.7% among the study population. Key factors associated with undiagnosed DM included medical history, higher BMI, and residing on smaller islands. Participants classified as overweight and obese were significantly more likely to have undiagnosed DM compared to those with a normal BMI (Adj. OR: 2.72, 95% CI: 1.40,5.30, p=0.003) for overweight; (Adj. OR: 2.43, 95% CI: 1.19,5.00, p=0.015) for obese. Individuals residing on smaller islands had a higher likelihood of undiagnosed DM compared to those on the main island (Adj. OR: 1.71, 95% CI: 1.03,2.85, p=0.039). Participants with a documented medical history were significantly less likely to have undiagnosed DM (Adj. OR: 0.21, 95% CI: 0.12,0.36, p<0.001). Conclusion: The high prevalence of undiagnosed DM among the PeKa B40 population underscores the urgent need for enhanced screening and early detection programs. Public health strategies should focus on targeted education campaigns, expanding healthcare infrastructure, and integrating opportunistic screening into routine healthcare interactions to improve early detection and management of DM.